PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN WAJIB KONVERGENSI IFRS PADA LAPORAN LABA RUGI KOMPREHENSIF (STUDI PADA PERUSAHAAN PERBANKAN YANG LISTING PADA BURSA EFEK INDONESIA TAHUN 2013-2014) - Fatin, Nurin Nandhi (Jurnal Bulletin, 2017)
The Effect of the Corporate Governance Structure on Disclosure of the IFRS Convergency Components in Comprehensive Profit and Comprehensive Statements (Study on Banking Companies Listed on Indonesia Stock Exchange 2013-2014). This study aims to analyze the level of compliance with mandatory disclosure IFRS at statement of comprehensive income in bank companies. Structure of corporate governance measured by the number of commissioners, the proportion of independent commissioners,the number of commissioners mettings, the number of audit committee members, the number of audit committee meetings, and competition audit committee. The level of IFRS mandatory at statement of comprehensive income is measured based on identified items of BAPEPAM Regulation Number VII.G.7. Under purposive sampling, secondary data of 40 annual report year 2013-2014 of in Indonesia Stock Exchange are selected. The multiple regression test showed that structure of corporate governance effects the level of compliance with mandatory disclosure convergences of IFRS. These result indicate that the level of compliance with mandatory disclosure convergence of IFRS at statement of comprehensive income in the bank companies is 55,8%. Corporate governanace structure variables that effect compliance is the number of commissioners, the number of audit committee members, and competition audit committee. Other variables, namely the proportion of independent commissioners,the number of commissioners mettings, and the number of audit committee meetings had no effect on the level compliance with mandatory disclosure convergence of IFRS at statement of comprehensive income